Multiple Measures Reveal Antiretroviral Adherence Successes and Challenges in HIV-Infected Ugandan Children - Haberer, Jessica E.; Kiwanuka, Julius; Nansera, Denis; Ragland, Kathleen; Mellins, Claude; Bangsberg, David R. (PLoS ONE, 2012)
Background: Adherence to HIV antiretroviral therapy (ART) among children in developing settings is poorly understood. Methodology/Principal Findings: To understand the level, distribution, and correlates of ART adherence behavior, we prospectively determined monthly ART adherence through multiple measures and six-monthly HIV RNA levels among 121 Ugandan children aged 2–10 years for one year. Median adherence levels were 100% by three-day recall, 97.4% by 30-day visual analog scale, 97.3% by unannounced pill count/liquid formulation weights, and 96.3% by medication event monitors (MEMS). Interruptions in MEMS adherence of $48 hours were seen in 57.0% of children; 36.3% had detectable HIV RNA at one year. Only MEMS correlated significantly with HIV RNA levels (r =20.25, p = 0.04). Multivariable regression found the following to be associated with ,90% MEMS adherence: hospitalization of child (adjusted odds ratio [AOR] 3.0, 95% confidence interval [CI] 1.6–5.5; p = 0.001), liquid formulation use (AOR 1.4, 95%CI 1.0–2.0; p = 0.04), and caregiver’s alcohol use (AOR 3.1, 95%CI 1.8–5.2; p,0.0001). Child’s use of co-trimoxazole (AOR 0.5, 95%CI 0.4–0.9; p = 0.009), caregiver’s use of ART (AOR 0.6, 95%CI 0.4–0.9; p = 0.03), possible caregiver depression (AOR 0.6, 95%CI 0.4–0.8; p = 0.001), and caregiver feeling ashamed of child’s HIV status (AOR 0.5, 95%CI 0.3–0.6; p,0.0001) were protective against ,90% MEMS adherence. Change in drug manufacturer (AOR 4.1, 95%CI 1.5–11.5; p = 0.009) and caregiver’s alcohol use (AOR 5.5, 95%CI 2.8–10.7; p,0.0001) were associated with $48-hour interruptions by MEMS, while second-line ART (AOR 0.3, 95%CI 0.1–0.99; p = 0.049) and increasing assets (AOR 0.7, 95%CI 0.6–0.9; p = 0.0007) were protective against these interruptions. Conclusions/Significance: Adherence success depends on a well-established medication taking routine, including caregiver support and adequate education on medication changes. Caregiver-reported depression and shame may reflect fear of poor outcomes, functioning as motivation for the child to adhere. Further research is needed to better understand and build on these key influential factors for adherence intervention development.
Keywords: Adherence to HIV; Antiretroviral therapy; Ugandan children